Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Practice: 4

Answer

$x=0$ $y=-3$

Work Step by Step

$5x - 2y = 6$ Equation #1 $-3x + y = -3$ Equation #2 Now solve the Equation #2 for $y$ $y=-3+3x$ Subtitute $y$ in Eq. #1 $5x-2(-3+3x)=6$ $5x+6-6x=6$ $5x-6x=6-6$ $x=0$ Now Substite $x$ in the Equation #1 to find $y$ $5(0)-2y=6$ $y=\frac{6}{-2}$ $y=-3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.